Replacement of Dietary Fishmeal Protein with Degossypolized Cottonseed Protein on Growth Performance, Nonspecific Immune Response, Antioxidant Capacity, and Target of Rapamycin Pathway of Juvenile Large Yellow Croaker (Larimichthys crocea) - Sheng Chen; Yuhang Tang; Zhou Zhang; Jichang Zheng; Yuliang He; Zhen Wang; Kangsen Mai; Qinghui Ai (Aquaculture Nutrition)
A 70-day feeding experiment was carried out to assess the replacement of dietary fishmeal (FM) protein with degossypolized cottonseed protein (DCP) on large yellow croaker (Larimichthys crocea) with initial body weight (13.09±0.50 g). Five isonitrogenous and isolipidic diets replaced fishmeal protein with 0%, 20%, 40%, 60%, and 80% DCP were formulated and named as FM (the control group), DCP20, DCP40, DCP60, and DCP80, respectively. Results displayed that weight gain rate (WGR) and specific growth rate (SGR) in the DCP20 group (263.91% and 1.85% d-1) were significantly increased compared with the control group (194.79% and 1.54% d-1) (P<0.05). Furthermore, fish fed the diet with 20% DCP significantly increased the activity of hepatic superoxide dismutase (SOD) compared with the control group (P<0.05). Meanwhile, the content of hepatic malondialdehyde (MDA) in the DCP20, DCP40, and DCP80 groups was significantly lower than that in the control group (P<0.05). The activity of intestinal trypsin in the DCP20 group was significantly degraded compared with that in the control group (P<0.05). The transcription of hepatic proinflammatory cytokine genes (interleukin-6 (il-6); tumor necrosis factor-α (tnf-α); and interferon-γ (ifn-γ)) in the DCP20 and DCP40 groups was significantly upregulated compared with that in the control group (P<0.05). As to the target of rapamycin (TOR) pathway, the transcription of hepatic target of rapamycin (tor) and ribosomal protein (s6) was significantly up-regulated, while the transcription of hepatic eukaryotic translation initiation factor 4E binding protein 1 (4e-bp1) gene was significantly downregulated in the DCP group compared with the control group (P<0.05). In summary, based on the broken line regression model analysis of WGR and SGR against dietary DCP replacement levels, the optimal replacement level was recommended to be 8.12% and 9.37% for large yellow croaker, respectively. These results revealed that FM protein replaced with 20% DCP could promote digestive enzyme activities and antioxidant capacity and further activate immune response and the TOR pathway so that growth performance of juvenile large yellow croaker was improved.